Reconstrução do Ligamento Patelofemoral no Síndrome Patelofemoral: conceitos atuais - Nuno Seabra Rodrigues (2021)
INTRODUCTION: Patellofemoral Syndrome (PFS) is a clinical entity associated to medial patellofemoral ligament (MPFL) injury. Many possible approaches are available to fix PFS. This review aims to describe the most proper indications to carry out medial patellofemoral ligament reconstruction (MPFLR). METHODS: A comprehensive search of the most recent literature was performed using combinations of the keywords MPFL, MPFLR, patellar dislocation and PFS treatment and indications. The Pubmed platform was used. ANATOMY: The MPFL is the main medial stabilizer of the patella in the first 30º of knee flexion, originating in a triangular area between the medial femoral epicondyle, the adductor tubercle and the gastrocnemius tubercle and inserting onto the superomedial face of the patella. MPFLR INDICATIONS: MPFLR is the treatment of choice for recurrent instability, especially in the absence of trochlear dysplasia, increased tibial tuberosity - trochlear groove (TT-TG) distance or patella alta. Under these conditions, alternative or in combination procedures are recommended, but isolated MPFLR is not. SURGICAL TECHNIQUES: There are several graft sources, such as gracilis, quadriceps, semintendinous, patellar tendon, allograft and artificial tendon. Neither of them have proved to have better results. There are several methods of fixation, on bone or soft tissue. Proper graft tensioning is a critical step in surgery. CONCLUSION: Given the efficacy of MPFLR, future research should aim to clarify more uniform criteria for patient selection to undergo this procedure.